Core–Shell CoSn@CoSnOx Nanoparticles Encapsulated in Hollow Carbon Nanocubes as Anodes for Lithium‐Ion Batteries. Issue 7 (18th May 2021) - Wu, Hao; Ma, Jie; Sun, Xiaolei; Su, Liwei; Sun, Bowen; Zheng, Lihua; Jiang, Yingying; Chen, Huan; Wang, Lianbang
Abstract : Sn‐based materials are considered as a promising candidate for anodes of lithium‐ion batteries (LIBs). However, rapid capacity fading associated with large volume expansion during cycling impedes the commercialization of Sn‐based anodes. Herein, a yolk–shell structure is designed via a thermal reduction method and following in situ surface oxidation. In this configuration, CoSn nanoparticles covered by a conformal surface oxide layer are encapsulated in hollow carbon nanocubes. When utilized as an anode material for LIBs, the CoSn@CoSnO x @C exhibits a high discharge capacity of 1177 mAh g −1 after 180 cycles at 0.2 A g −1 and a capacity retention of 86.7% after 500 cycles at a higher current density of 1 A g −1 . The investigation demonstrates that the outstanding electrochemical performance of the composite anodes can be attributed to the synergistic effects of the yolk–shell structure, nanosized CoSn alloy core, and conformal surface oxide layer. This elaborately designed structure can be extended to other alloy‐type anode materials to tackle the capacity decay induced by volume expansion. Abstract : Herein, a yolk–shell structure is synthesized via a thermal reduction method and subsequent in situ surface oxidation. In this configuration, CoSn nanoparticles covered by a conformal surface oxide layer are encapsulated in hollow carbon nanocubes. This elaborate structure is designed to tackle the rapid capacity fading associated with large volume expansion of Sn‐based anodes during cycling.